Application of Appropriate Technology in Optimizing Tilapia Hatchery in Fish Farmer Groups in Pudak Payung Village, Semarang - Ratnawati, Beata; Sayekti, Ayutyas; Febrinda, Andi Early; Indriastuti, Cecilia Eny; Wicaksono, Sandy Satria (Riwayat: Educational Journal of History and Humanities, 2024)
This program aims to implement appropriate technology, specifically, the Recirculating Aquaculture System (RAS), to optimize tilapia breeding in the fish farmer groups in Pudak Payung Village, Semarang. The RAS technology is applied to improve efficiency, effectiveness, and productivity in the breeding process, hoping to enhance fish seed quality and survival rate. The results show that this technology has reduced water usage, and decreased seed mortality rates. The training provided has also improved the knowledge and skills of farmers in managing the RAS system and water quality. The level of satisfaction among the served community is extremely high, although challenges related to excellent seeds, access to capital, marketing, and harvest management still pose some obstacles. In conclusion, RAS technology has great potential to improve the welfare of tilapia farmers, but further support from the government, academics, and stakeholders is needed for the sustainability and development of the program.